Distribution and behavior of Anopheles maculatus and its potential as a Malaria vector in Indonesia - Riyani Setiyaningsih; Sapto Prihasto; Fahmay Dwi Ayuningrum; Arif Suryo Prasetyo; Mega Tyas Prihatin; Sekar Negari; Siti Alfiah; Lulus Susanti; Evi Sulistyorini; Jery Cahyandaru; Triwibowo Ambar Garjito (Universitas Ahmad Dahlan, 2023)
Background: Anopheles maculatus is one of the mosquito species that has been confirmed as a malaria vector in Indonesia. The potential of a mosquito as a vector is influenced by its behavior. Information on the distribution and behavior of An. maculatus needs to be carried out to determine the potential for malaria transmission transmitted by the species in an area. The study aimed to obtain information on the distribution, behavior, and potential of maculatus as a malaria vector in several provinces in Indonesia. Method: Mosquito collection was carried out using human-landing collection, animal-baited trap, cattle-bait, light-trap, and resting morning. A survey of mosquitoes was carried out in 29 provinces in Indonesia. Mosquitoes were identified for the species and detected the blood-sucking behavior with an Enzyme-linked immunosorbent assay and the presence of Plasmodium using a Polymerase Chain Reaction. Results: The results showed that An. maculatus was found in the Riau Islands, Lampung, Bangka Belitung, West Java, Central Java, East Java, and Central Sulawesi. Anopheles maculatus has known to suck the blood of humans and animals with a predominance of animals. Anopheles maculatus is also known to suck blood outdoors predominantly. In general, the activity of An. maculatus sucking blood begins around 18.00 in the evening. Central Java Province was the province with the highest density of An. maculatus mosquitoes, thereby increasing the potential for transmission of malaria cases. Conclusion: Anopheles maculatus was spread in Riau Islands, Lampung, Bangka Belitung, West Java, Central Java, East Java, and Central Sulawesi. This species was known to suck the blood of people and humans, and its blood-sucking activity starts around 18.00 in the evening.